2019
DOI: 10.1101/772640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polyunsaturated fatty acid analogues differentially affect cardiac Nav, Cav, and Kv channels through unique mechanisms

Abstract: 20The cardiac ventricular action potential depends on several voltage-gated ion channels, 21 including Nav, Cav, and Kv channels. Mutations in these channels can cause Long QT 22 Syndrome (LQTS) which increases the risk for ventricular fibrillation and sudden cardiac 23 death. Polyunsaturated fatty acids (PUFAs) have emerged as potential therapeutics for 24 LQTS because they are modulators of voltage-gated ion channels. Here we 25 demonstrate that PUFA analogues vary in their selectivity for human voltage-g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 46 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…1f, Table I). The reason for the higher concentration of N-AT used in these experiments is that N-AT has an apparent lower affinity to the IKs channel compared with DHA-GLY and Lin-Gly 42 .…”
Section: Pufa and Pufa Analogues Shorten Qt Interval In Ex-vivo Guinea Pig Hearts With Druginduced Lqt2mentioning
confidence: 99%
See 1 more Smart Citation
“…1f, Table I). The reason for the higher concentration of N-AT used in these experiments is that N-AT has an apparent lower affinity to the IKs channel compared with DHA-GLY and Lin-Gly 42 .…”
Section: Pufa and Pufa Analogues Shorten Qt Interval In Ex-vivo Guinea Pig Hearts With Druginduced Lqt2mentioning
confidence: 99%
“…Xenopus oocytes, in addition to activating KCNQ1/KCNE1 channels 42 . Altogether, this suggests that natural and modified PUFAs shorten QT interval and APD in guinea pig hearts by targeting several ion channels.…”
Section: And Cav12 Expressed Inmentioning
confidence: 99%
“…There is also a need to test the effect of PUFA analogs on physiological systems such as cardiomyocytes, neurons or whole hearts. In two recent papers the effect of PUFA analogs has been tested on NaV, CaV, cardiomyocytes and guinea pig hearts (Bohannon et al 2020a, Skarsfeldt et al 2020. Bohannon et al 2020 reported that the same PUFA analogs that can activate KV7.1 + E1 can inhibit NaV and CaV channels.…”
Section: Future Directionsmentioning
confidence: 99%
“…PUFAs have been shown to activate the large-conductance Ca 2+ -and voltage-gated K + (Slo1 BK) channel with a nanomolar EC50 (21)(22)(23). In addition, the voltage-gated potassium channel KV7.1 can be either potentiated or inhibited by PUFAs and PUFA derivatives depending on the nature of the lipid (24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that dietary supplementation of ω-3 fatty acids can help patients with cystic fibrosis (40). In addition, PUFAs are being designed as a potential treatment for patients with Long QT syndrome type 1 (24,27,29,30). ASICs are potentially interesting targets for the inhibition of pain and the inhibition of cell death in both ischemia and neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%